Modification of foam morphology in powder extrusion molding of alumina with thermally expandable microspheres - Forstner, Thomas; Drummer, Dietmar (MSE 2024 - Materials Science and Engineering Congress, 2024)
The indirect manufacturing technologies of powder injection molding (PIM) or powder extrusion molding (PEM) are promising ways for the efficient production of complex, near-net-shape metal or ceramic parts. These special processes, which combine the geometric flexibility and efficiency of polymer technology with the desired final properties of specific metals or ceramics after sintering, already address manifold applications throughout industry, the medical sector or everyday life. However, this variety can be further expanded via a combination of these processes with other techniques from polymer technology, such as chemical or physical foaming, which are commonly used to produce lightweight polymer foam materials. For this study, thermally expandable microspheres (TEM) were used within the continuous PEM process for the creation of cellular ceramic profiles with tailorable foam properties in a multi-step-process. Therefore, a highly filled polymer feedstock was processed with rising TEM-contents and varying screw speeds. The extruded profiles were evaluated regarding their pore morphologies and densities in their green and sintered states via sub-µ-computed tomography (sub-µ-CT). The amount of TEM’s added was found to directly influence the porosity of the green and sintered part, allowing a tailorable porosity as Figure 1 demonstrates. Furthermore, the pore morphology given by the templates in the green state also manifests in the sintered state, leading to porosities of up to 37 % within the sintered par